Hubungan Asupan Energi dan Asupan Zat Gizi Makro Terhadap Kejadian Obesitas pada Remaja - Rahayu, Dewi; Nasution, Napila Ulia Sari; Sri Mulyani; Dewi Erowati; Yolahumaroh (Jurnal Kesehatan Komunitas, 2025)
The prevalence of obesity in Pekanbaru City among adolescents aged 16-18 years in 2018 was 4.87%. Obesity in adolescents is mainly caused by excessive food intake. The purpose of this study was to determine the relationship of energy intake and macronutrient intake to the incidence of obesity in SMA Negeri 2 Pekanbaru. This type of research is descriptive analytic research with cross-sectional design. The research sample was 44 respondents obtained using stratified random sampling technique. Data collection used food recall questionnaires and anthropometric measurements. Data analysis used the spearman correlation test. The results showed that 29.5% of respondents were obese, 56.8% had excess energy intake, 75% had excess protein intake, 72.7% had excess fat intake, and 56.8% had excess carbohydrate intake. The results of bivariate analysis showed that there was no relationship between energy intake (p=0.068), protein intake (p=0.085), fat intake (0.081), and carbohydrate intake (0.068) with the incidence of obesity in adolescents. It is expected that health workers provide education about balanced nutrition to students so that optimal nutritional status for adolescents can be realized.